2010
DOI: 10.1158/1078-0432.ccr-09-1773
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Array Comparative Genomic Hybridization in Sporadic and Celiac Disease–Related Small Bowel Adenocarcinomas

Abstract: Purpose: The molecular pathogenesis of small intestinal adenocarcinomas is not well understood. Understanding the molecular characteristics of small bowel adenocarcinoma may lead to more effective patient treatment.Experimental Design: Forty-eight small bowel adenocarcinomas (33 non-celiac disease related and 15 celiac disease related) were characterized for chromosomal aberrations by high-resolution array comparative hybridization, microsatellite instability, and APC promoter methylation and mutation status. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 51 publications
5
62
0
3
Order By: Relevance
“…Among the alterations seen in this group, deletions at chromosome 18q were the most common shared feature (58% in the CIN group, 30% of all investigated carcinomas) and were commonly associated with gains at chromosomes 20q and 7 as well as with losses of chromosomes 4q, 8p, and 17p (Table 1). Our finding of 30% 18q deletions among all investigated small bowel adenocarcinomas is in contrast with a previous matrix CGH study by Diosdado et al 38 reporting o10% of 18q deletions in 48 small intestinal adenocarcinoma, whereas the frequencies of deletions at 4q, 8p, 17p, and gains at chromosomes 7 and 20 were similar to those of our study. The reason for this discrepancy is not clear.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Among the alterations seen in this group, deletions at chromosome 18q were the most common shared feature (58% in the CIN group, 30% of all investigated carcinomas) and were commonly associated with gains at chromosomes 20q and 7 as well as with losses of chromosomes 4q, 8p, and 17p (Table 1). Our finding of 30% 18q deletions among all investigated small bowel adenocarcinomas is in contrast with a previous matrix CGH study by Diosdado et al 38 reporting o10% of 18q deletions in 48 small intestinal adenocarcinoma, whereas the frequencies of deletions at 4q, 8p, 17p, and gains at chromosomes 7 and 20 were similar to those of our study. The reason for this discrepancy is not clear.…”
Section: Discussionsupporting
confidence: 57%
“…The reason for this discrepancy is not clear. It may be explained by sampling variation, and in part result from the high number of celiac disease-associated carcinomas (15/48) included in the study by Diosdado et al 38 (1/37 in our study), which have been shown to follow a somewhat different genetic pathway than nonceliac disease-related sporadic carcinomas. 38,39 Chromosome 18q harbors the SMAD4 gene, a mediator of TGFb signaling, which was previously described as a mutational target for a variety of cancers, including small bowel adenocarcinoma.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Young age of onset and detection of MSI are typical for the development of SBA in the setting of HNPCC. Our data and the findings of two other studies (31,32) identifying MSI in 67 and 73% of CD-associated carcinomas, respectively, show that these features also occur in CDassociated SBAs. Therefore, CD should be included in the differential diagnosis of SBAs exhibiting MSI.…”
Section: ------------------------------------------------------------supporting
confidence: 85%
“…A microsatellite instability (MSI) analysis was performed as previously described [29] using the MSI Analysis System (MSI Multiplex System, Version 1.1, Promega Corp., Madison, WI) consisting of five nearly monomorphic mononucleotide markers (BAT-25, BAT-26, . Separation of polymerase chain reaction (PCR) products was performed by capillary electrophoresis using an ABI 3130 DNA sequencer (Applied Biosystems, Foster City, CA) and analysis was performed using GeneScan 3100 (Applied Biosystems, Foster City, CA).…”
Section: Microsatellite Instability Analysismentioning
confidence: 99%